Dimethyl Cardamonin from Fruits of Campomanesia reitziana D. Legrand Promotes Gastroprotection and Gastric Healing Effects in Rodents. Issue 12 (8th November 2022) - Cury, Benhur Judah; Boeing, Thaise; Somensi, Lincon Bordignon; Campos, Adriana; Cechinel‐Filho, Valdir; de Souza, Priscila; da Silva, Luisa Mota
Abstract: Campomanesia reitziana D. Legrand (Myrtaceae) displays antiulcer properties when given to rodents. The major active chemical components of C. reitziana are chalcones, including 4′, 6′‐dihydroxy‐2′‐methoxy‐3′, 5′‐dimethylchalcone or dimethyl cardamonin (DMC); therefore, we hypothesized that this compound could have antiulcer effects and the present study aimed to evaluate its gastroprotective and gastric healing properties. DMC was isolated from the fruits of C. reitziana, and its gastroprotective effect was evaluated by ethanol and indomethacin‐induced gastric ulcer models in mice (0.1 mg/kg, i.p. and 1 and 3 mg/kg, p.o.). Oxidative stress and inflammatory parameters were analyzed in the gastric tissue. Moreover, its gastric healing effect was evaluated in rats. In addition, the compound's mode of action was evaluated in vivo and in vitro by measuring H + ‐K + ‐ATPase activity. Finally, the cytotoxic potential of DMC was tested in fibroblasts and human gastric adenocarcinoma cells. The DMC reduced the ethanol‐induced gastric ulcer in mice by 77 %, increased the adhered mucus, and reduced lipoperoxides levels. The block of nonprotein sulfhydryls (NP‐SH) compounds by pretreatment with N‐ethylmaleimide (NEM), the inhibition of nitric oxide synthase with Nω‐nitro‐L‐arginine methyl ester hydrochloride (L‐NAME), or the antagonism of α2 receptor using yohimbine reversed the gastroprotective effects of DMC. Furthermore, DMC reduced the acidity of gastric content in pylorus‐ligated rats but did not change H +, K + ‐ATPase (isolated from rabbit) activity in vitro . DMC reduced the lesion area in acetic acid‐induced ulcers and decreased myeloperoxidase activity. DMC did not change the viability of fibroblast cells (L929) but reduced the viability of human gastric adenocarcinoma cells (AGS). The results confirmed that DMC could significantly enhance the gastric healing process and prevent ulcers due to improving protective factors on the gastric mucosa and reducing gastric acid secretion. Abstract :